2012
DOI: 10.1111/j.1525-1470.2012.01734.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics of Becker’s Nevus in Children: Report of 118 Cases from Italy

Abstract: We performed a retrospective study covering a 10-year period (January 1997-January 2007) on children referred to our unit or followed up for Becker's nevus (BN). The aim of this study was to better define the characteristics of BN in childhood, when this hypermelanosis is more frequent than the limited number of studies might suggest. Our data show that BN in children has predilection sites similar to those in adults, but hypertrichosis is rarer. Sun exposure does not appear to play an etiopathogenetic role. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 11 publications
(15 reference statements)
3
38
3
Order By: Relevance
“…However, there are only a few systematic studies of its clinicopathologic features234. The immunohistochemical observations of other indexes are nearly unavailable in BN except androgen receptor and melanocyte25.…”
Section: Introductionmentioning
confidence: 99%
“…However, there are only a few systematic studies of its clinicopathologic features234. The immunohistochemical observations of other indexes are nearly unavailable in BN except androgen receptor and melanocyte25.…”
Section: Introductionmentioning
confidence: 99%
“…Becker nevi are occasionally congenital but more commonly appear during adolescence due to a localized increase in androgen receptor sensitivity within the nevus [61]. A recent retrospective study of 118 children in Italy with a diagnosed Becker nevus showed a nearly equal distribution among sexes (47 % male) in contrast to the common assumption of predominance in adolescent males [62]. Hypertrichosis also was present in only one-third of cases as compared to the presence of terminal hairs in the Becker nevi of 70 % of young Italian men [63].…”
Section: Other Pigmented Lesionsmentioning
confidence: 83%
“…Most studies in adults show a five times greater incidence in men than women, but few other studies have revealed a female predominance [2]. The higher incidence in men reported in adult case studies has not been found in children [3]. Histological evaluation reveals acanthosis, epidermic hyperpigmentation, papillomatosis, arrector pili muscle hyperplasiam and melanophages in dermis [4].…”
Section: Discussionmentioning
confidence: 99%